Seasonal migration and feminization of farm management: Evidence from India - S. Chandrasekhar; Soham Sahoo; Hema Swaminathan (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2017)
This paper explores the association between short-term migration in the household and feminization of farm management in rural India. The analysis uses a nationally representative data set covering 35,604 rural Indian households in the year 2013. There is gender disaggregated information on who operates land in addition to the presence of a short-term migrant in the household. We model the labor outcomes of women as reflected by their participation as major decision-makers (main operator) or minor decision makers (associated operator) on the household operational holding. Overall, we find that women are less likely than men to be either main or an associated operator. However, in households with a short-term migrant, the probability of a woman being a decision maker as an operator increases. These results are robust to endogeneity and sample selection concerns. Our study highlights the importance of unpacking the feminization process to better understand the role of women as farm managers.
Keywords: Q1; R2; J1; 330; Feminization of agriculture; Female farm managers; Seasonal migration; Agricultural households; Operational holdings; India